Clinical efficacy of endodontic protocols on reducing cultivable bacteria and endotoxin in infected root canal in patients submitted to head and neck radiotherapy: a randomised clinical trial - de Rabello, Diego Guilherme Dias [UNESP]; Valera, Marcia Carneiro [UNESP]; Corazza, Bruna Jordão Motta [UNESP]; dos Santos, Lúcio Murilo [UNESP]; Carvalho, Claudio Antônio Talge [UNESP] (Springer Nature, 2023)
Objectives: Assess the efficacy of biomechanical preparation using a reciprocating system followed by final irrigation protocols, then intracanal medication, on reducing endotoxins and cultivable bacteria of infected teeth in irradiated patients. Materials and methods: Twenty-two infected single-rooted canals in patients submitted to head and neck radiotherapy were prepared by reciprocating motion and 2.5% NaOCl. Patients were randomly divided into two groups of 11 patients before the final irrigation protocol: apical positive pressure (APP) or passive ultrasonic activation (PUA). Both groups were treated in two sessions, using Ca(OH)2 as intracanal medication for 14 days. Root canal content sampling was performed after canal access (S1), after biomechanical preparation plus the irrigation protocol (S2), and after intracanal medication (S3). Chromogenic limulus amoebocyte lysate assay measured endotoxin levels (EU/mL), and bacterial load was determined by culture techniques (CFU/mL). Results: Treatment protocols reduced bacterial counts after S2 in both groups (p = 0.01). S3 differed from S1 (p = 0.01), but not from S2 (p = 0.4). Endotoxin levels were reduced in both groups after S2 (P = 0.03) and were lower in S3 than in S2, with significant differences in the APP group (p = 0.03). Conclusions: Biomechanical preparation using a reciprocating system and 2.5% NaOCl in irradiated teeth, followed by the irrigation protocol (APP or PUA), demonstrated efficacy in reducing endodontic contaminants. Ca(OH)2 as intracanal medication should be performed in irradiated patients with infected root canals. Clinical relevance: This clinical study demonstrated that endodontic treatment in irradiated patients is efficacious at reducing bacterial load and endotoxin levels.
Keywords: Cancer; Endodontic treatment; Endotoxin; Periapical periodontitis; Radiotherapy; Randomised controlled trial; Ultrasonic